2013
DOI: 10.2478/s11687-013-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

The helminth infracommunities of the wood mouse (Apodemus sylvaticus) two years after the fire in Mediterranean forests

Abstract: SummaryParasites have been recognized as indicators for natural or man-induced environmental stress and perturbation. In this article, we investigated the role of two non-exclusive hypotheses on the response of helminths of wood mice to fire perturbation: 1) a reduction of the helminth infracommunity (species richness) in post-fire areas due to the temporal lack of worms with indirect (complex) life cycles linked to intermediate hosts that are more specialized than the final host, and 2) an increase of the abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
(38 reference statements)
0
10
2
Order By: Relevance
“…Fourteen helminth species were found in this study, a number equal to or higher than those reported in other studies (Portolés et al, 2000;Torres et al, 2003;Fuentes et al, 2004a, b;Torre et al, 2013) but lower than those reported by Fuentes et al (2007aFuentes et al ( , 2010 for various enclaves of the Iberian Peninsula.…”
Section: Discussioncontrasting
confidence: 50%
“…Fourteen helminth species were found in this study, a number equal to or higher than those reported in other studies (Portolés et al, 2000;Torres et al, 2003;Fuentes et al, 2004a, b;Torre et al, 2013) but lower than those reported by Fuentes et al (2007aFuentes et al ( , 2010 for various enclaves of the Iberian Peninsula.…”
Section: Discussioncontrasting
confidence: 50%
“…In the shortterm, forest fires significantly reduce richness of helminths in the long-tailed field mouse Apodemus sylvaticus Linnaeus, increase prevalence of monoxenous (life-cycle restricted to a single host species) helminths but decrease prevalence of heteroxenous helminths (life-cycle dependent on multiple host species; Torre, Arrizabalaga, Feliu, & Ribas, 2013). The latter response is likely caused by intermediate hosts being rare or absent in intensively burnt forests (Torre et al, 2013). Habitat disturbance by off-road vehicles and habitat fragmentation are associated with high prevalence of Sin Nombre virus (SNV) in deer mice and an increased encounter rate among hosts is the suggested mechanism (Langlois, Fahrig, Merriam, & Artsob, 2001;Mackelprang, Dearing, & Jeor, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances also have major impacts on pathogen prevalence in wildlife, but it remains inconclusive if disturbance increases or decreases prevalence, transmission among animals, and/or potential transmission to and infection risk of humans. In the short‐term, forest fires significantly reduce richness of helminths in the long‐tailed field mouse Apodemus sylvaticus Linnaeus, increase prevalence of monoxenous (life‐cycle restricted to a single host species) helminths but decrease prevalence of heteroxenous helminths (life‐cycle dependent on multiple host species; Torre, Arrizabalaga, Feliu, & Ribas, ). The latter response is likely caused by intermediate hosts being rare or absent in intensively burnt forests (Torre et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…To investigate connection with this disease, infections with pinworm S. muris, a ubiquitous nematode that parasitizes mainly in the large intestines of wild and experimental rats (Rattus norvegicus), was employed. The lifecycle of S. muris is direct, and host animals are infected with the nematode via an oral intake of their eggs; the prepatent period of this nematode is 7−8 days (Stahl, 1961;Taffs, 1976;Torre et al, 2013). In the present study, 100 S. muris eggs were orally administered to 5-week-old fa/fa rats at the pre-diabetic stage, and eggs were detected 2 weeks after inoculation in the perianal region of all fa/fa rats in the infection group.…”
Section: Discussionmentioning
confidence: 99%